Progressive reduction of circulating B lymphocytes in patients with X-linked lymphoproliferative disease (XLP) - Baré, Patricia (2016)
Fil: Baré, Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Medicina Experimental. Academia Nacional de Medicina de Buenos Aires. Instituto de Medicina Experimental; Argentina